Avaliação histométrica e microtomográfica da reparação óssea em defeitos de tamanho críticos em calvárias de ratas osteoporóticas preenchidos com a associação de doxiciclina e osso bovino particulado - Alves, Luís Henrique Theodoro (2019)
Osteoporosis is a chronic skeletal disease that causes imbalance in the process of bone repair, intensifying osteoclastic activity and causing an increase in bone fragility. Doxycycline has the property of inhibiting osteoclastogenesis in situations of normal bone metabolism. Thus, the objective of this study was to evaluate the local application of Doxycycline, in the form of a gel, associated or not to bovine bone particulate (Bio-Oss®) on bone repair in calvarial defects of osteoporotic rats, by means of of microtomographic and histometric analysis. From a total of 58 animals with approximately 8 weeks of age weighing between 180 and 300g, forty-four were submitted to ovariectomy surgery (OVX) and another 14 animals underwent false surgery (SHAM-ovariectomy), in which the ovaries were only exposed, and repositioned at the place of origin. Eight animals were used to validate the model of characterization of osteoporosis, being 4 OVX and 4 SHAM. A defect of 6 mm in diameter was made with trephine in calvaria of the animals and these were randomly divided into 5 groups, with 10 animals, according to the treatment received: SHAM (Fictitious ovariectomy); OVX-CS (Blood clot); OXX-DOX (Doxycycline); OVX-BIO (Bio-Oss®); OVX-BODOX (Bio-Oss® associated with Doxycycline). Five animals from each group underwent euthanasia at 4 and 8 weeks postoperatively. In the microtomographic and histometric analyzes, the bone neoformation was calculated in the region of the defect. The values obtained were submitted to analysis of variance (ANOVA) and Tukey's test (p <0.05). The results of the microtomographic analysis showed that the newly formed bone volume (BV) in the 4-week period was statistically higher in the OVX-BIO group (6.0300 mm3) when compared to the other groups (p <0.05). In the 8- week period, the OVX-DOX (3.2035 mm 3), OVX-BODOX (3.2435 mm 3) and OVX-BIO (5.5041 mm 3) groups were statistically larger than the SHAM control group (p <0.05). In the histometric analysis, in the 4-week period, the area of neoformed bone (OA) of the OVX-BIO group (13.592%) was statistically higher (p <0.05) than the other groups. In the 8-week period, the OVX-DOX (9.542%), OVX-BIO (10.420%) and OVX-BODOX (4.708%) groups were statistically larger (p <0.05) than the SHAM group (1.944%). The results obtained allow us to conclude that the isolated 10% Doxycycline gel showed results similar to the results of its association with bovine bone when used locally in critical defects of calves of osteoporotic rats. However, it showed inferior results when filling with isolated bovine bone in the initial periods.